RAC3 down-regulation sensitizes human chronic myeloid leukemia cells to TRAIL-induced apoptosis - Colo, Georgina Pamela (2007)
The nuclear receptor coactivator RAC3 plays important roles in many biological processes and tumorigenesis. We found that RAC3 is over-expressed in human chronic myeloid leukemia cells K562, which are normally resistant to TRAIL-induced apoptosis. RAC3 down-regulation by siRNA rendered these cells sensitive to TRAIL-induced cell death. In addition to the up-regulation of TRAIL receptors, the process involves Bid, caspases and PARP activation, loss of mitochondrial membrane potential, and release of AIF, cytochrome c and Smac/DIABLO to the cytoplasm. We conclude that RAC3 is required for TRAIL resistance and that this anti-apoptotic function is independent of its role in hormone receptor signaling.